1971
DOI: 10.2307/1934734
|View full text |Cite
|
Sign up to set email alerts
|

Territory and Breeding Density in the Great Tit, Parus Major L.

Abstract: This paper describes an investigation into whether or not spring territorial behavior was limiting the breeding density of a population of Great Tits on Wytham Estate, near Oxford. The analysis of distances between neighboring nests showed that nest sites were more spaced out than would be expected from a random distribution; this indicated that interactions between the birds produced at least a local density—limiting effect. In 2 successive years, established territorial pairs were removed from a stable sprin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
392
2
3

Year Published

1983
1983
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 679 publications
(419 citation statements)
references
References 52 publications
22
392
2
3
Order By: Relevance
“…A short experiment reported by Dhondt (1971) also indicated that supplementary feeding in winter can increase the breeding density. On the other hand, Krebs (1971) found food supplementation in the winter to have no effect on the size of the breeding population. However, his results are not conclusive because his experiment lasted only one winter, wich happened to coincide with a good beechmast crop.…”
mentioning
confidence: 90%
“…A short experiment reported by Dhondt (1971) also indicated that supplementary feeding in winter can increase the breeding density. On the other hand, Krebs (1971) found food supplementation in the winter to have no effect on the size of the breeding population. However, his results are not conclusive because his experiment lasted only one winter, wich happened to coincide with a good beechmast crop.…”
mentioning
confidence: 90%
“…Augé, Chilvers, Moore, & Davis, 2014; Weber et al, 2015), even when habitat quality is 3 sub-optimal (Krebs, 1971;Merkle, Cherry, & Fortin, 2015). Fidelity to foraging areas may 4 have long-term advantages for individual fitness, particularly in unpredictable environments 5 (Switzer, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The territory, or defended section of the home range, can be described in terms of two main factors: nesting requirements and food resources, with territory size varying in relation to the environment so as to maximize the fitness of the individual (Patterson 1980). Thus, territory size can be viewed in terms of two competing hypotheses: as a response to resource density (food availability), so that the territory contains enough food to satisfy energetic requirements (Schoener 1968, Gill & Wolf 1975; or as a response to defense costs, where the variation in territory size occurs because more competitors are attracted to areas rich in resources, and such areas are, therefore, more costly to defend per unit area (Krebs 1971). The analysis of home range is based on the utilization density of the range, and is defined as the minimum area in which an animal has a given probability (for example of 95%) of being found (Worton 1995).…”
Section: Introductionmentioning
confidence: 99%